2005
DOI: 10.1111/j.0001-6349.2005.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of oligosaccharide variants of alpha‐fetoproteins produced by normal fetuses and fetuses with trisomy 21

Abstract: The transference of the AFP-L3 fraction might be relatively high in the placentas of women carrying a trisomy 21 fetus, and this could be the one of the reasons for the increase in the percentage of AFP-L3 in the maternal serum in pregnancies with a trisomy 21 fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…AFP-L3 is predominantly found in the serum of mothers of children with DS -its transplacental passage is probably promoted relative to the other 2 isoforms. It was later proven that the use of AFP-L3 instead of AFP increases the sensitivity of the triple test [13,14], while the use of AFP-L2 and AFP-L3 improves the detectability of open neural tube defects and abdominal wall defects [15]. AFP-L3 is the predominant isoform of AFP found in hepatocellular carcinoma based on hepatic cirrhosis and hepatitis [3].…”
Section: Mrna Variants and Isoforms Of Afpmentioning
confidence: 99%
“…AFP-L3 is predominantly found in the serum of mothers of children with DS -its transplacental passage is probably promoted relative to the other 2 isoforms. It was later proven that the use of AFP-L3 instead of AFP increases the sensitivity of the triple test [13,14], while the use of AFP-L2 and AFP-L3 improves the detectability of open neural tube defects and abdominal wall defects [15]. AFP-L3 is the predominant isoform of AFP found in hepatocellular carcinoma based on hepatic cirrhosis and hepatitis [3].…”
Section: Mrna Variants and Isoforms Of Afpmentioning
confidence: 99%
“…Additionally, the maternal serum AFP level was decreased, which may be associated with specific AFP transport defects. Yamamoto et al [ 25 ] also confirmed that the placental AFP-L3 level in pregnant women carrying fetuses with trisomy 21 was elevated, which may explain the increased serum level of AFP-L3 in these women. Therefore, we speculate that the increased serum level of AFP-L2 in pregnant women carrying fetuses with trisomy 21 in early pregnancy is similar to that of AFP or AFP-L3.…”
Section: Discussionmentioning
confidence: 92%
“…Yamamoto et al posited that the placental transfer of the AFP-L3 component in women carrying a fetus with trisomy 21 may be relatively high, which might be one of the causes for the elevated serum AFP-L3 levels in these pregnant women 36 . In addition, Yamamoto 37 did not detect a correlation between maternal serum AFP-L3 and AFP MoMs (r = 0.006) and did not observe a significant correlation between serum AFP level and AFP-L3 percentage.…”
Section: Discussionmentioning
confidence: 99%